Improving Firm Value to Dividend Policy Evidence of Indonesia Public Company in Emerging Market - Ulfi Pristiana; Muis Murtadho (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Investors constantly aim for a rise in firm value and sustainability to ensure favorable returns on their capital investments. Nonetheless not every company issues dividends. This research seeks to investigate how dividend payments influence firm value, concentrating on 517 firms listed on the Indonesia Stock Exchange during the period from 2014 to 2023. Data was collected from secondary sources, particularly via annual reports released on the Indonesia Stock Exchange. The results show that policies regarding dividend payments greatly impact a company's value. Notably, the research indicates that businesses with reduced dividend payments often have a more substantial effect on firm value, while those with increased dividend distributions do not exhibit a significant impact. Additionally, the effects of dividend policies differ among various industrial sectors. For example, in the energy and non-cyclical consumer sectors, dividend distributions greatly influence firm value. In contrast, sectors like basic materials, industrials, and real estate do not show a statistically meaningful connection. These findings provide important insights for corporate leaders, indicating that regular and strategic dividend disbursements can cultivate investor confidence and allegiance. Consequently, this confidence from investors could foster the firm's long-term development and enhance its valuation in the capital market